Insight into Corporate Governance in Islamic Finance: A Systematic Review of Literature - Rehman, Quanita; Ali, Dr. Akhtiar (The journal of contemporary issues in business and government, 2022)
The concept of corporate governance (CG) in Islamic banking (IB) has gained attention of researchers in the last two decades. This review paper aims to provide broad and comprehensive review of existing literature on CG in Islamic banks(IBs). The research on CG in IBs has mainly been empirical conducted mostly in Gulf Cooperation Council (GCC) and South Eastern region with a few conceptual studies. A sound theoretical base for Islamic CG studies is still missing. The results suggesting role of Shariah Supervision are elusive. The impact of emerging economies and country legal systems as antecedents of CG have not been thoroughly covered in the literature. In the field of research this topic needs to be covered more rigorously and exhaustively. CG in IBs is an emerging area of research and lack comprehensive review studies. Owing to the fact, this review paper aims to provide broad, comprehensive review of existing literature on corporate governance in IBs. which can be employed for further research about the subject matter.